Effectiveness of Tabletop Disaster Exercise (TDE) as A Means to Improve The Competence of Medical Personnel in Disaster Emergency Response: A Literature Review - Fibran Aryan Nahya; Ahmad Syarif (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Background: Indonesia is one of the countries with a high risk of natural disasters with 20,380 events between 2020-2024. The high number of disasters that occur will have an impact on the high number of casualties that must be handled by medical personnel. Often what happens in the field is the limited number of medical personnel who handle victims, making the impression of poor service for the community and the lack of competence of medical personnel related to disaster management. Therefore, one of the efforts to improve the competence of medical personnel in disaster emergency response is through Tabletop Disaster Exercise (TDE) training. Objective: To determine the effectiveness of the TDE method to improve the competence of medical personnel in disaster management. Methods: The method used was a literature review taken from several sources with a limit of 2018- 2024. Results and Discussion: The implementation of training with the TDE method is proven to increase knowledge and competence in disaster management. This is because TDE has several advantages, namely, real scenario-based simulation, a stress-free training environment, and the development of coordination between teams. Conclusion: TDE is one of the effective disaster management training methods to improve the competence of medical personnel in disaster management.